2021
DOI: 10.1016/j.yebeh.2021.107939
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral adverse events with brivaracetam, levetiracetam, perampanel, and topiramate: A systematic review

Abstract: To understand the currently available post-marketing real-world evidence of the incidences of and discontinuations due to the BAEs of irritability, anger, and aggression in people with epilepsy (PWE) treated with the anti-seizure medications (ASMs) brivaracetam (BRV), levetiracetam (LEV), perampanel (PER), and topiramate (TPM), as well as behavioral adverse events (BAEs) in PWE switching from LEV to BRV. Methods: A systematic review of published literature using the Cochrane Library, PubMed/MEDLINE, and Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 72 publications
1
27
1
Order By: Relevance
“…The prevalence of patients reporting psychiatric TEAEs in this study was similar to the pooled analysis of the seven phase II and III interventional clinical studies of perampanel presented in this paper, but was higher than a pooled analysis of the three pivotal phase III perampanel clinical trials alone (24.4% vs 24.3% vs 15.3%, respectively) [31]. A recent systematic review of brivaracetam, levetiracetam, perampanel, and topiramate, reported higher mean rates of irritability, anger, and aggression in phase IV realworld studies compared with clinical development trials [32]. It was concluded that this observation was not surprising, given the confines of controlled trials and the fact that real-world studies may allow inclusion of more patients with epilepsy at risk of these events.…”
Section: Discussioncontrasting
confidence: 59%
“…The prevalence of patients reporting psychiatric TEAEs in this study was similar to the pooled analysis of the seven phase II and III interventional clinical studies of perampanel presented in this paper, but was higher than a pooled analysis of the three pivotal phase III perampanel clinical trials alone (24.4% vs 24.3% vs 15.3%, respectively) [31]. A recent systematic review of brivaracetam, levetiracetam, perampanel, and topiramate, reported higher mean rates of irritability, anger, and aggression in phase IV realworld studies compared with clinical development trials [32]. It was concluded that this observation was not surprising, given the confines of controlled trials and the fact that real-world studies may allow inclusion of more patients with epilepsy at risk of these events.…”
Section: Discussioncontrasting
confidence: 59%
“…Both PER and BRV are among the ASMs traditionally associated with the strongest risk of behavioural adverse events. Although the incidence of these side effects is higher with PER than with BRV [ 49 ], the lack of analyses by individual TEAEs did not allow us to state whether the difference in the tolerability profile was driven by the risk of behavioural adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…18 Interestingly, the BRV efficacy is similar to those reported in long-term follow-up trials using other ASMs 33,34 and appears to be comparable to that described in a previous retrospective study of BRV. 35,36 Few studies investigating BRV efficacy in the real-world setting have reached 12 months of follow-up. A retrospective Spanish study, which included adult patients with focal epilepsy, reported an overall response in 40% of patients, with 17.2% reporting seizure freedom after 12 months.…”
Section: Discussionmentioning
confidence: 99%